Unraveling the Nanoscopic Organization and Function of Central Mammalian Presynapses With Super-Resolution Microscopy - Carvalhais, Lia G. (Front Neurosci, 2021)
The complex, nanoscopic scale of neuronal function, taking place at dendritic spines, axon terminals, and other minuscule structures, cannot be adequately resolved using standard, diffraction-limited imaging techniques. The last couple of decades saw a rapid evolution of imaging methods that overcome the diffraction limit imposed by Abbe’s principle. These techniques, including structured illumination microscopy (SIM), stimulated emission depletion (STED), photo-activated localization microscopy (PALM), and stochastic optical reconstruction microscopy (STORM), among others, have revolutionized our understanding of synapse biology. By exploiting the stochastic nature of fluorophore light/dark states or non-linearities in the interaction of fluorophores with light, by using modified illumination strategies that limit the excitation area, these methods can achieve spatial resolutions down to just a few tens of nm or less. Here, we review how these advanced imaging techniques have contributed to unprecedented insight into the nanoscopic organization and function of mammalian neuronal presynapses, revealing new organizational principles or lending support to existing views, while raising many important new questions. We further discuss recent technical refinements and newly developed tools that will continue to expand our ability to delve deeper into how synaptic function is orchestrated at the nanoscopic level.